Androgen actions on the human hair follicle: perspectives. Issue 3 (28th September 2012) - Inui, Shigeki; Itami, Satoshi
Abstract Androgens stimulate beard growth but suppress hair growth in androgenetic alopecia (AGA). This condition is known as 'androgen paradox'. Human pilosebaceous units possess enough enzymes to form the active androgens testosterone and dihydrotestosterone. In hair follicles, 5α‐reductase type 1 and 2, androgen receptors (AR) and AR coactivators can regulate androgen sensitivity of dermal papillae (DP). To regulate hair growth, androgens stimulate production of IGF‐1 as positive mediators from beard DP cells and of TGF‐β1, TGF‐β2, dickkopf1 and IL‐6 as negative mediators from balding DP cells. In addition, androgens enhance inducible nitric oxide synthase from occipital DP cells and stem cell factor for positive regulation of hair growth in beard and negative regulation of balding DP cells. Moreover, AGA involves crosstalk between androgen and Wnt/β‐catenin signalling. Finally, recent data on susceptibility genes have provided us with the impetus to investigate the molecular pathogenesis of AGA.